The complementing and facilitating nature of common ground in acquisitions – why task and human integration are still necessary in the presence of common ground. Issue 20 (12th November 2016) - Dao, Mai Anh; Bauer, Florian; Strobl, Andreas; Matzler, Kurt; Eulerich, Marc
Abstract : This paper focuses on common ground as an informal coordination mechanism during post-merger integration. In particular, we investigate if shared knowledge and shared beliefs between acquirer and target trigger a self-coordination mechanism among employees and therefore can act as an alternative path to human integration in mature industries. We are arguing that a dynamic research approach capturing a period of one year from deal closing onwards is beneficial to better understand the integration autonomy dilemma and the necessary coordination mechanisms. Based on case study research, we find that common ground is a double-edged sword with benefits and weaknesses. While in a first period common ground fosters coordination and allows for efficient task integration, a sole reliance on common ground without any human integration measures and management commitment has clear disadvantages in the long run. It is observable that the commitment to change of employees disappears and organizational resistance occurs.